Emergence agitation during recovery from intracranial surgery under general anaesthesia: a protocol and statistical analysis plan for a prospective multicentre cohort study. Issue 4 (21st April 2015) - Yan, Li-Mei; Chen, Han; Yu, Rong-Guo; Wang, Zhu-Heng; Zhou, Guan-Hua; Wang, Yong-Jin; Zhang, Xia; Xu, Ming; Chen, Lu; Zhou, Jian-Xin; ,
Abstract : Introduction: Emergence agitation after intracranial surgery is an important clinical issue during anaesthesia recovery. The aim of this multicentre cohort study is to investigate the incidence of emergence agitation, identify the risk factors and determine clinical outcomes in adult patients after intracranial surgery under general anaesthesia. Additionally, we will deliberately clarify the relationship between postoperative pneumocephalus and agitation. Methods and analysis: The present study is a prospective multicentre cohort study. Five intensive care units (ICUs) in China will participate in the study. Consecutive adult patients admitted to the ICUs after intracranial surgery will be enrolled. Sedation-Agitation Scale (SAS) or Richmond Agitation-Sedation Scale (RASS) will be used to evaluate the patients 12 h after the enrolment. Agitation is defined as an SAS score of 5–7, or an RASS score of +2 to +4. According to the maximal SAS and RASS score, patients will be divided into two cohorts: the agitation group and the non-agitation group. Factors potentially related to emergence agitation will be collected at study entry, during anaesthesia and operation, during postoperative care. Univariate analyses between the agitation and the non-agitation groups will be performed. The stepwise backward logistic regression will be carried out to identify the independent predictors of agitation. Patients will be followed up for 72 h after the operation. Accidental self-extubation of the endotracheal tube and removal of other catheters will be documented. The use of sedatives and analgesics will be collected. Ethics and dissemination: Ethics approval has been obtained from each of five participating hospitals. Study findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: NCT02318199.